Pragmalinguistic Analysis of the Category of Impersonality in the Uzbek Language - Eshmurodova, Gulchehra (The Lingua Spectrum, 2025)
This article explores the pragmalinguistic features of impersonality in the Uzbek language, focusing on how impersonal constructions function within communicative contexts. The study highlights the structural, pragmatic, and semantic characteristics of impersonality, examining its role in expressing indirectness, politeness, generalization, and speaker detachment. Various impersonal forms such as passive constructions, indefinite-personal expressions, and modal structures are analyzed from the standpoint of pragmatics. Special attention is given to how impersonality contributes to communicative strategies, allowing speakers to modulate responsibility, soften statements, and maintain social harmony. The findings emphasize that impersonality in Uzbek is not only a grammatical phenomenon but also a pragmatic tool used to shape interpersonal relations and discourse dynamics. The research also sheds light on the socio-psychological functions of impersonality and demonstrates how these constructions reflect culturally embedded norms such as respect, modesty, and avoidance of confrontation in Uzbek communicative practices. The paper illustrates how impersonal constructions operate in formal discourse (official documents, academic writing), media texts, instructional genres, and everyday interpersonal communication. Through examples and discourse analysis, the study shows that impersonality is not merely a grammatical phenomenon but serves as a crucial pragmatic tool for constructing cooperative interaction, managing interpersonal distance, and ensuring communicative harmony. Overall, the findings indicate that impersonality in Uzbek plays an essential role in shaping discourse strategies, signalling social alignment, and regulating speaker–hearer dynamics.